Legal Construction of Anti Eco-SLAPP Reinforcement in Indonesia - Banulita, Mia; Utami, Titik (Yuridika, 2021)
A Strategic Lawsuit Against Public Participation (SLAPP) does not only occur in the environmental sector but in any situation in which an act aims to stop or eliminate the opposition of public participation to certain policies. In the environmental sector, Eco-SLAPP aims to use fear and intimidation to silence people who commit aggression against environmental policies and/or certain interests through reporting/filing complaints or lawsuits to court. Therefore, the Anti Eco-SLAPP concept in Law Number 32 of 2009 was formed to provide protection against the act of Eco-SLAPP as it harms people who fight for a good and healthy environment. Unfortunately, Law Number 32 of 2009 exhibits weakness regarding its substance and process in fulfilling Anti Eco-SLAPP. In terms of substance, Article 2(a) Law Number 32 of 2009 has not given the state responsibility to implement Anti Eco-SLAPP, and Article 66 Law Number 32 of 2009 has not regulated good faith as the reason a person cannot be prosecuted criminally or sued civilly. Neither has it regulated protection from administrative action, the motion strike/dismissal process, or SLAPP Back to prevent early Eco-SLAPP actions. In addition, the implementation of Anti Eco-SLAPP is often misinterpreted since it is unable to distinguish pure criminal acts and actions to fight for the environment based on good faith. Therefore, it is necessary to construct an Anti Eco-SLAPP law based on the weaknesses of the existing Law Number 32 of 2009, so as to reinforce the implementation of Anti Eco-SLAPP in Indonesia.